Zn-doped nickel iron (oxy)hydroxide nanocubes passivated by polyanions with high catalytic activity and corrosion resistance for seawater oxidation - Kim, So Jung; Choi, Heechae; Ryu, Jeong Ho; Kim, Kang Min; Mhin, Sungwook; Nayak, Arpan Kumar; Bang, Junghwan; Je, Minyeong; Ali, Ghulam; Chung, Kyung Yoon; Na, Kyeong-Han; Choi, Won-Youl; et al. (Elsevier BV, 2023)
Electrochemical water splitting to produce hydrogen fuel is a promising renewable energy-conversion technique. Large-scale electrolysis of freshwater may deplete water resources and cause water scarcity worldwide. Thus, seawater electrolysis is a potential solution to the future energy and water crisis. In sea-water electrolysis, it is critical to develop cost-effective electrocatalysts to split seawater without chloride corrosion. Herein, we present zinc-doped nickel iron (oxy)hydroxide nanocubes passivated by negatively charged polyanions (NFZ-PBA-S) that exhibits outstanding catalytic activity, stability, and selectivity for seawater oxidation. Zn dopants and polyanion-rich passivated surface layers in NFZ-PBA-S could effec-tively repel chlorine ions and enhance corrosion resistance, enabling its excellent catalytic activity and stability for seawater oxidation.(c) 2023 Science Press and Dalian Institute of Chemical Physics, Chinese Academy of Sciences. Published by ELSEVIER B.V. and Science Press. All rights reserved.